Attentional guidance by salient feature singletons depends on intertrial contingencies. - Olivers, C; Humphreys, G (2003)
Evidence that salient feature singletons guide attention only when the target and the singleton frequently coincide has been taken to suggest that selection of singletons is under top-down control: Observers strategically use an attentional set sensitive to the singleton being a target. Changing the singleton-target (or singleton-distractor) coincidence also changes the opportunity for facilitative and disruptive intertrial effects to occur. The authors show that benefits and costs associated with certain singletons depend at least partly on the preceding trial type. Results are in line with dimensional weighting and perceptual priming accounts, which propose a (semi-) automatic transfer of dimensional activity from one trial to the next. Results also indicate that priming is set independently for each dimension.